Gestational Trophoblastic Disease Diagnosis Delayed by the Hook Effect. Issue 4 (October 2015) - Cormano, Julia; Mackay, Gillian; Holschneider, Christine
Abstract : BACKGROUND: A "hook effect" resulting from saturation of antibodies used in pregnancy tests can occur at human chorionic gonadotropin (hCG) levels above 500, 000 milliinternational units/mL, resulting in falsely negative values. CASE: A 34-year-old woman, gravida 5 para 3, presented to the emergency department after heavy bleeding. Ultrasonogram revealed a uterine mass, urine pregnancy test result was negative, and endometrial biopsy inconclusive. The patient was discharged and presented 10 days later with recurrent bleeding. Urine pregnancy test result was again negative, but serum hCG was 581 milliinternational units/mL. Serial dilution revealed an actual hCG higher than 5 million milliinternational units/mL. She was diagnosed with gestational trophoblastic disease. CONCLUSION: Awareness of the risk of a false-negative pregnancy test result when hCG levels are extremely high may prevent delayed diagnosis of gestational trophoblastic disease. Abstract : A "hook effect" resulting from extremely high human chorionic gonadotropin levels results in false-negative urine pregnancy test results and delayed diagnosis of gestational trophoblastic disease.